Letter from Viktor Homburger to Max and Georg Bredig, February 6, 1941 - Homburger, Viktor (1941)
Letter from Viktor Homburger (1903-1986) to his father-in-law, Georg Bredig (1868-1944), and his brother-in-law, Max Bredig (1902-1977). The Letter provides updates on the Homburgers' circumstances in the Gurs internment camp and is numbered No. 10.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986; Gurs (Concentration camp); Homburger, Viktor, 1888-1968; Nazi concentration camps